2016
DOI: 10.1016/j.nima.2016.03.093
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-fast silicon detectors (UFSD)

Abstract: Abstract-We report on measurements on Ultra-Fast Silicon Detectors (UFSD) which are based on Low-Gain Avalanche Detectors (LGAD). They are n-on-p sensors with internal charge multiplication due to the presence of a thin, low-resistivity diffusion layer below the junction, obtained with a highly doped implant. We have performed several beam tests with LGAD of different gain and report the measured timing resolution, comparing it with laser injection and simulations. For the 300μm thick LGAD, the timing resolut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 98 publications
(49 citation statements)
references
References 8 publications
1
48
0
Order By: Relevance
“…Previous results for single sensors before and after irradiation can be found in Refs. [2][3][4][5][6][7]. In this paper, the previous results have been confirmed and extended to results of LGAD arrays, including uniformity scans of the pad surface.…”
Section: Introductionsupporting
confidence: 74%
See 1 more Smart Citation
“…Previous results for single sensors before and after irradiation can be found in Refs. [2][3][4][5][6][7]. In this paper, the previous results have been confirmed and extended to results of LGAD arrays, including uniformity scans of the pad surface.…”
Section: Introductionsupporting
confidence: 74%
“…The breakdown voltage for arrays was found to be reduced (about 200 V for medium dose) due to the absence of a JTE around each pad as explained above. Beam tests and laboratory measurements have been performed in the past both for 300 µm, 50 µm and 35 µm thick LGADs, mostly single-pad devices [2][3][4][5][6][7]. In particular, results of laboratory studies on the devices of the same run used here can be found in Refs.…”
Section: Lgad Sensorsmentioning
confidence: 99%
“…Much higher gains compromise the S/N ratio, because bulk shot noise is also amplified by the amplification structure (called excess noise) such that there is an optimal gain for maximum signal-to-noise (see for instance [36] or [42]). Prototype LGAD structures have been fabricated [38,43] with relatively large pads (from 8×8 mm 2 to 1×1 mm 2 ), rather than pixels, mainly to validate the underlying models and simulations of the achievable time resolution. LGAD weighting field simulations and measurements: (a) slew rate as a function of detector thickness for different amplification gains (simulation); (b) comparison of time resolutions from weighting field simulations (WF2) and from test beam measurements using constant fraction discrimination.…”
Section: Lgad Structuresmentioning
confidence: 99%
“…The WF2 simulations for 1x1µm 2 are underlined by the dashed line only to guide the eye. The data are taken from [38], [43], [44], [33], and [42].…”
Section: Lgad Structuresmentioning
confidence: 99%
“…(b) Comparison of time resolutions from simulations (WF2) and from test beam measurements. Data points from [55], [56], [57], [58], and [59].…”
Section: Fast Timing With Pixelsmentioning
confidence: 99%